Undergraduate nursing education during the COVID-19 pandemic - Araújo, Agostinho Antônio Cruz; Amaral, Jackeline Vieira; Araújo Filho, Augusto Cézar Antunes de; Nunes, Benevina Maria Vilar Teixeira (Revista Cuidarte, 2020)
Betacoronavirus SARS-CoV-2 appeared in December 2019 in the city of Wuhan, China¹. The easy transmissibility of the virus, as well as the lack of means to immunize the population and effective treatment, justify the adoption of social isolation measures in order to combat contagion by the virus.Currently, faced with the pandemic of the new coronavirus, it was noted that Higher Education Institutions had to adapt to continue some of their academic activities. An example of this was the partial return of classes in master's and doctorate programs, as well as training and updating courses and videoconferences.  Distance Education  appears as a possibility of education for academics and professionals through the sharing of knowledge anywhere, requiring only one means of access².Translated with www.DeepL.com/Translator (free version)How to cite this article: Araújo, Agostinho Antônio Cruz; Amaral, Jackeline Vieira; Filho, Augusto Cézar Antunes de Araújo; Nunes, Benevina Maria Vilar Teixeira.  O ensino de graduação em enfermagem durante a pandemia da COVID-19. Revista Cuidarte. 2021;12(1):e1290. http://dx.doi.org/10.15649/cuidarte.1290
Keywords: Education, Nursing; Coronavirus Infections; Students, Nursing